DETERMINAN KECURANGAN PENGELOLAAN DANA DESA DI KECAMATAN BAHOROK, KABUPATEN LANGKAT - Br. Sinuraya, Novita Ria; Azhar, Iqlima; Meutia, Tuti (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2025)
This research aims to determine the influence of transparency, community participation and accountability on fraudulent management of village funds in Bahorok sub-district, Langkat Regency. This type of research uses quantitative research, the data source for this research uses primary data. The population and sample for this research are villages in Bahorok sub-district, totaling 18 villages as a population and the sample taken in this research is 72 officials who understand better and are involved in financial activities in the village. This research uses purposive sampling, namely a certain sampling technique based on certain considerations or criteria. The data obtained was analyzed using SPSS (Statistical Package For Social Sciences) analysis techniques. The equation model analyzed is multiple linear regression analysis, and classical assumption testing and hypothesis testing (T test, F test and Coefficient of Determination (R2). The results obtained from this research are: (1) transparency has a significant negative effect on fraudulent management of village funds, (2) community participation has a positive effect on fraudulent management of village funds, (3) accountability has a significant negative effect on fraudulent management of village funds, (4) transparency, community participation and accountability have a significant effect on fraudulent management of village funds. This research has limitations that can be taken into consideration by future researchers, in order to improve further research where many village officials do not have adequate educational background and do not have good competence in managing finances. Researchers provide suggestions for future researchers who are expected to be able to develop and perfect further research in the future